Air travel and COVID-19 prevention: Fasten your seat belts, turbulence ahead - Grobusch, M. P.; Schaumburg, F.; Frey, A. (Travel Medicine and Infectious Disease, 2020)
It is widely accepted that the epidemiological curve of COVID-19 can only be flattened in a team action, taking into account all factors that could contribute to the spread of the virus. At the same time, individual sectors (e.g. entertainment and sporting industries, hospitality business, education, aviation) lobby, even take legal action, to be excluded from tough lockdown measures by showing that they do not contribute significantly to the spread of SARS-CoV-2. Therefore, balanced evidence-based decision-making becomes more and more fundamental to justify any restrictions of both private and professional life.